Если враг не сдается: [роман] / Михаил Нестеров - Нестеров Михаил Петрович (Спецназ ГРУ, 2003)
Экземпляры: ф11 (20180609) / Инвентарный номер: 56170 / Цена: 45.00 / Сис.шифр: Р2 / Авт.знак: Н 56 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6